Effect of organic materials on grain yield and soil properties in maize (Zea mays)wheat (Triticum aestivum) cropping system - SHARMA, M P; GUPTA, J P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1994-95 and 1995-96 to evaluate some locally available organic plant residues as suppleruentry source of nutrients in maize (Zea mays L.)-wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system. Grain yield, nutrients uptake by maize increased significantly with increase in levels of NPK. Response to 100% NPK was 1.51 and 1.36 tonnes/ha over control yield of 1.81 and 1.62 tonnes/ha in maize and wheat crops respectively. Integration of 75% N through chemical fertilizers + 25% N through organic sources gave equal yield to 100% NPK in maize. The farmyard manure and white popinac leaves had registered their residual effect on succeeding wheat crop by producing equivalent yield as 100% NPK. Among diferent organic sources, farmyard manure proved superior to blackgram (Phaseolus mungo L.) straw followed by white popinac leaves while wheat straw proved inferior source of N substitution. The water-holding capacity, organic carbon, available nitrogen and phosphorus increased with increase in the organic residues while available K and bulk density decreased. The values were more evident in integration of 50% N from chemical fertilizer + 50% N through organic sources, viz farmyard manure, white popinac leaves and blackgram straw.